Banks' loans to reduce the risk of leasing lines - Nozimov Eldor Anvarovich (Universitas Muhammadiyah Sidoarjo, 2020)
In this article, theoretical views on leasing lending, improving lending practices and ways to reduce risks, as well as current problems and their practical solutions and prospects for future development will be widely considered.